Peran Manajemen Pendidikan dalam Peningkatan Kualitas Pembelajaran Pada Madrasah Tsanawiyah Negeri 1 Palembang - Saputra, Ade Akhmad; Efriliyanti, Lia; Hakim, Aulia; Satera, Alihan (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
The focus of this research is the role of education management in improving the quality of learning at Madrasah Tsanawiyah Negeri 1 Palembang. The role of educational management is very influential on the success of learning. This research is a field research using a qualitative approach. The type of data used is qualitative data. There are two kinds of data sources used, namely primary data sources and secondary data. Meanwhile, to obtain data using the method of observation, documentation and interviews. For data processing using descriptive qualitative data analysis. The results of this study are First, the implementation of the education management function has been carried out properly, in accordance with the conditions of the school concerned. This means that all of these management functions have been carried out but due to limited supporting factors in the form of infrastructure and conditions of school personnel, the management functions are carried out as well as possible. Second, the educational management function that has been carried out at Madrasah Tsanawiyah Negeri 1 Palembang shows an increase in the quality of education and employee performance, although there are still some obstacles but it does not really affect work professionalism and the resulting quality shows quite satisfactory results in terms of input and output.